Autonomous underwater vehicles : design and practice - Ehlers, Frank 1969- (The Institution of Engineering and Technology, 2020)
"The recent development of advanced processing capabilities and higher yield power supplies means that Autonomous Underwater Vehicle (AUVs) are finding novel and increasingly advanced applications in research, military and commercial settings. This timely book provides a state-of-the-art overview of AUV design and practice. Focusing on the interplay between design and practice, it comprehensively covers control and navigation, communication and cooperation, and methodologies and applications where AUVs are used for education, research, biological and oceanographic studies, surveillance purposes, and military, security, and industrial tasks. The book covers key concepts for maritime engineers and navigation researchers and professionals, and is a useful reference for control and robotics researchers working on AUVs"--